2006
DOI: 10.1590/s1519-566x2006000400019
|View full text |Cite
|
Sign up to set email alerts
|

Primeiro registro de Lipaphis pseudobrassicae Davis (Hemiptera: Aphididae) e sua associação com insetos predadores, parasitóides e formigas em couve (Cruciferae) no Brasil

Abstract: -This study describes the fauna of predator insects, parasitoids and ants associated with aphids on kale (Brassica oleracea L. var. acephala D.C.) in organic system. The aphid was identified as Lipaphis pseudobrassicae Davis, and this is the first record of the species attacking kale in Brazil. Primary parasitism by Diaeretiella sp. and Aphidius sp. and hyperparasitism by Aphydencyrtus sp., Alloxysta sp., Pachyneuron sp. and Syrphophagus sp. were observed. Twenty species of Coccinellidae were collected, and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
2
17
0
3
Order By: Relevance
“…A total of 1,296 specimens of natural enemies were identified, and 57.2% were classified as predators represented by the Coccinellidae (26.5%), Syrphidae (27.8%) Chrysopidae (2.9%) and 42.8% as parasitoids distributed in Braconidae (84.9%), Eulophidae (9%) and Encyrtidae (6.1%). The families of predators found in this study corroborate those reported by Resende et al (2006), who captured insect species of Coccinellidae, Chrysopidae and Syrphidae in kale (Brassica oleracea L. var. acephala D.C.) cultivated in the organic system.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A total of 1,296 specimens of natural enemies were identified, and 57.2% were classified as predators represented by the Coccinellidae (26.5%), Syrphidae (27.8%) Chrysopidae (2.9%) and 42.8% as parasitoids distributed in Braconidae (84.9%), Eulophidae (9%) and Encyrtidae (6.1%). The families of predators found in this study corroborate those reported by Resende et al (2006), who captured insect species of Coccinellidae, Chrysopidae and Syrphidae in kale (Brassica oleracea L. var. acephala D.C.) cultivated in the organic system.…”
Section: Resultssupporting
confidence: 90%
“…The other sampling methods captured 32.0%. Resende et al (2006) captured 17 species of Coccinellidae from kale plants using the yellow sticky traps method. According to Dowell and Cherry (1981), the yellow sticky traps are more efficient in coccinellid collections than the visual method; Civolani and Pasqualini (2003) reported that the manual collection method is more efficient than using yellow sticky traps to monitor aphids.…”
Section: Resultsmentioning
confidence: 99%
“…They are found feeding primarily on aphids that infest citrus, subtropical fruit trees, corn, alfalfa, cotton, grapes, lettuce, ornamentals, and also many wild plants (Ghahari et al 2008). Resende et al (2006) reported that A. exotica is the most abundant species of Syrphidae collected from leaves of cabbage feeding on aphids.…”
mentioning
confidence: 99%
“…3) are similar to the results found by Celini and Vaillant (2004), who observed that population growth curves for A. gossypii in cotton plants of similar physiological ages present similar behavior. Resende et al (2004) also recorded a population peak of alate A. gossypii when cauliflower plants (Brassica oleracea Linnaeus) were 77 days old. On the other hand, Pinto et al (2000) found that green peach aphid (Myzus persicae (Sulzer)) tends to present a single population peak during the crop cycle of the potato (Solanum tuberosum Linnaeus).…”
Section: Within-plant Distribution Of Cotton Aphidmentioning
confidence: 95%